PKC-theta in regulatory and effector T-cell functions - Brezar, Vedran; Tu, Wen Juan; Seddiki, Nabila (Frontiers in Immunology, 2015)
One of the major goals in immunology research is to understand the regulatory mechanisms that underpin the rapid switch on/off of robust and efficient effector (Teff) or regulatory (Tregs) T-cell responses. Understanding the molecular mechanisms underlying the regulation of such responses is critical for the development of effective therapies. T-cell activation involves the engagement of T-cell receptor and co-stimulatory signals, but the subsequent recruitment of serine/threonine-specific protein Kinase C-theta (PKC-θ) to the immunological synapse is instrumental for the formation of signalling complexes, that ultimately lead to a transcriptional network in T cells. Recent studies demonstrated that major differences between Teffs and Tregs occurred at the immunological synapse where its formation induces altered signalling pathways in Tregs. These pathways are characterized by reduced recruitment of PKC-θ, suggesting that PKC-θ inhibits Tregs suppressive function in a negative feedback loop. As the balance of Teffs and Tregs has been shown to be central in several diseases, it was not surprising that some studies revealed that PKC-θ plays a major role in the regulation of this balance. This review will examine recent knowledge on the role of PKC-θ in T-cell transcriptional responses and how this protein can impact on the function of both Tregs and Teffs.